CARA PANDANG JURNALIS PEREMPUAN DALAM RUANG PRIBADI - Diah Amelia (Politeknik Negeri Media Kreatif, 2014)
This research explores the Standpoint of women journalists in the magazine business and economics on the profession and also whether they have an understanding of journalism in a gender perspective. This study is a qualitative research strategy and case study data collecting technique through interview, observation and literature. Standpoint theory hold on women's experiences that will take them to have some understanding. This theory emphasizes the reciprocal relationship between communication behavior and attitudes. The results presented that women have a standpoint that journalists consider important the existence of gender awareness and sensitivity within him to be able to produce news that defending the interests of women in business and economics magazine. However, patriarchal and capitalist culture contained in the private and public areas are still holding their efforts.